(untitled) (Homiletic, 2016)
Prior to the establishment of the DMin degree at Aquinas Institute in 1996, there was no terminal degree in preaching from a Catholic institution of higher learning. Since that time, eighteen Catholic women have obtained doctorates in preaching. In November of 2014, the author surveyed that population to ask: Who are these women who are prepared for leadership in homiletics? What is their current situation? And what are their hopes, frustrations, and dreams? This essay summarizes the responses to those questions in order to open the discussion about Catholic women in homiletic leadership.